Synthesis of Cellulose Stearate Ester as Wet Strength Agent for Synthesis of Bio-polybag from Oil Palm Empty Fruit Bunch - Kurniawan, Eddy; Mulyawan, Rizka; Tri Agusna PA, Angga; Armadani, Wika; Ginting, Zainuddin (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2022)
Biodegradable polybags are an alternative to overcome the weakness of synthetic polybags because of their degradation properties. Oil palm empty fruit bunches contain a lot of cellulose so that they can be used as a biodegradable polybag. Wet Strength serves to increase the physical strength of bio-polybags when exposed to water (in wet conditions) so that water content stability is required. In this study, Cellulose Stearate Esters were synthesized in an effort to increase the stability of the water content in bio-polybags. Cellulose Stearate Esters are synthesized through a transesterification reaction between -Cellulose isolated from Oil Palm Empty Fruit Bunches (EFB) with methyl stearate. The synthesis of cellulose stearate esters was carried out by refluxing for 2 hours using methanol solvent with various catalysts Na2CO3 5, 10, 15, 20 mg and with volume variations of methyl stearate 5, 10, 15. And the best variation was determined based on the degree of substitution test, namely with variations Na2CO3 catalyst 20 mg and volume of methyl Stearate 15 ml, amounting to 1.95. The result of the synthesis, namely cellulose stearate, was tested for functional groups by FT-IR spectroscopy and surface morphology using SEM. The formation of cellulose stearate is supported by the FT-IR spectrum in the wavenumber region of 3468.01 cm-1 indicating an OH group, 3062.96 cm-1 indicating a CH stretching group, 1695.43 cm-1 indicating a C=O group, cm-1 indicating a CH bending group, 1095.57cm-1 indicates a COC group, 609.51cm-1 indicates a (CH2)n4 group. The results of surface morphology analysis using SEM showed that the surface of cellulose stearate looked homogeneous, more regular and had denser cavities than -Cellulose